1981
DOI: 10.1161/01.cir.64.5.1018
|View full text |Cite
|
Sign up to set email alerts
|

Reat-time inferior vena caval ultrasonography: normal and abnormal findings and its use in assessing right-heart function.

Abstract: SUMMARY We studied the inferior vena cava (IVC) as an index of right-heart function in 111 patients. A two-dimensional echocardiographic sector was used to visualize the IVC, and its M-mode cursor was used to generate a time-motion record of the IVC size and pulsation. Normal subjects had a small presystolic A wave (less than 125% of the end-diastolic IVC dimension), a small systolic V wave (less than 140% of the enddiastolic IVC dimension), and a 50% inspiratory decrease in IVC dimension. GRAY-SCALE B-SCAN UL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 11 publications
4
76
2
Order By: Relevance
“…The method that seems more accurate was developed by Lichtenstein, and calculates IVC diameter longitudinally at end-expiration and end-diastole and during the R wave on electrocardiogram (ECG), 2 cm before the right atrium and with the M-mode on short axis view (Lichtenstein & Jardin, 1994). The estimation of RAP using IVC diameter and its respiratory collapse has been shown to correlate better with central venous pressure (CVP) in patients with RV dysfunction and PH (Mintz et al, 1981). It seems that since the normal respiratory augmentation in venous return is limited by RV enlargement, normal IVC diameter variations are reduced, increasing diagnostic accuracy of this technique.…”
Section: Conventional Hemodynamic Measurements In Icumentioning
confidence: 99%
“…The method that seems more accurate was developed by Lichtenstein, and calculates IVC diameter longitudinally at end-expiration and end-diastole and during the R wave on electrocardiogram (ECG), 2 cm before the right atrium and with the M-mode on short axis view (Lichtenstein & Jardin, 1994). The estimation of RAP using IVC diameter and its respiratory collapse has been shown to correlate better with central venous pressure (CVP) in patients with RV dysfunction and PH (Mintz et al, 1981). It seems that since the normal respiratory augmentation in venous return is limited by RV enlargement, normal IVC diameter variations are reduced, increasing diagnostic accuracy of this technique.…”
Section: Conventional Hemodynamic Measurements In Icumentioning
confidence: 99%
“…In the medical literature, there is no agreement on whether the IVC increases or decreases in diameter during the Valsalva maneuver [1][2][3][4][5][6][7] . In a study on the diameter of the IVC measured by ultrasound, Grant et al [1] acknowledged this controversy and observed a decrease of IVC caliber during the Valsalva maneuver with a maximum increase at the end of the forced inspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have included healthy volunteers, 2 continuous ambulatory peritoneal dialysis patients, 3 hemodialysis patients, 4,5 healthy volunteers at phlebotomy centers, 6 and critically ill patients in intensive care units. 7,8 In addition, the locations of IVC measurements differ across studies [9][10][11][12][13][14][15][16][17][18][19] (Table 1). This study aimed to determine if the degree of IVC collapsibility (also referred to as ''caval index'') varied within the same subject at commonly measured sites.…”
mentioning
confidence: 99%